Internalization of the Value of Traditional Malay Education in Madrasah as the Foundation for Generation Z Moral Development - Anggraini, Fitri; Soraya, Nyayu; Anggara , Baldi (Journal of Educational Sciences, 2026)
Generation Z faces moral degradation challenges due to negative digital content exposure and weakening understanding of traditional values, positioning madrasah strategically to internalize Islamic values based on Malay local wisdom. This research aims to identify relevant Malay traditional education values, describe internalization processes, and formulate an integrative model as the foundation for Generation Z's moral development in madrasah. The research method employs a qualitative approach with descriptive-analytical library research on 2020-2025 literature through content analysis techniques. Results indicate that tauhid values, noble character, tawasuth, tasamuh, and tawazun are internalized through comprehensive strategies including contextual exemplary, project-based learning, spiritual habituation, reflective dialogue, and individual counseling integrating formal and hidden curriculum. The integrative model combining philosophical, institutional, pedagogical, socio-cultural, psychological, and technological dimensions proves effective in forming religious character reflected through worship consistency, rule compliance, discipline, and social responsibility. Recommendations include strengthening tripartite school-family-community collaboration, continuous teacher competency development, and digital technology utilization aligned with Malay oral tradition preservation to maintain traditional values relevance for Generation Z.